Tobacco harm reduction: The potential to reduce the risk from smoking: a six-month exposure response study on switching from cigarettes to tobacco heating system (THS) - de La Bourdonaye, Guillaume; Costanzo, Roberta; Haziza, Christelle (Medical Word, 2020)
The primary goal of the Exposure Response Study (ERS) was to generate direct evidence that actual use of Philip Morris International’s smoke-free alternative to cigarettes, Tobacco Heating System (THS), can reduce smokers’ risk of harm compared to continuing to smoke cigarettes. In the study eight biomarkers of potential harm (BoPH) were measured, to provide further evidence on effects of current adult smokers switching to THS. Each of the BoPH were selected because they are associated with smoking-related diseases, are negatively impacted by smoking and are reversible following smoking cessation. Given the study hypothesis, that the eight BoPH which cover eight different pathways of disease would change favorably, similarly to what is reported in the literature following smoking cessation. Therefore all eight BoPH were included and tested as co-primary endpoints.In total 984 smokers were randomized to either switch to THS use, or continue to smoke cigarettes. The eight BoPH were assessed over a period of six months in an ambulatory setting. The results showed that when smokers switched to THS, all eight BoPH showed a changes similar to what is seen following smoking cessation, and five of the eight BoPH were statistically significant better in smokers who switched to THS than smokers who continued to smoke cigarettes. This led to the conclusion that switching from cigarettes to THS-use likely reduces a smoker’s risk of tobacco-related disease and may present less risk of harm compared to continued smoking.
Keywords: tobacco heating system (THS), biomarkers of potential harm (BoPH), smoke-free products, tobacco harm reduction